MYERS-BRIGGS TYPE INDICATOR (MBTI): EXAMINING BEHAVIOURAL ASPECTS OF EXECUTIVES IN 'IT' - N. Rajagopal (ABHIGYAN, 2008)
Personality tests have been widely used as an indicator for measuring performance of individuals. Among many personality type indicators, Myers-Briggs Type Indicator (MBTI) is a widely used as a strong instrument to learn individual differences for the last five decades. It's application in the industry has been widely discussed. The indicator helps organisations to utilise the talent of its employees within the organisation. The present study tries to analyse the personality dimensions of middle level executives in the 'IT' based on the MBTI types of indicators. The study was conducted among 200 middle level executives. The basic inference emerging from this study is that the dominant personality indicators of executives in the IT sector are basically extroverts, which is related to their judging capacity. As competition is getting momentum in Indian IT industry, such studies will be helpful to understand the personality types of executives in the industry. "Whatever circumstances of your life, the understanding of the type can make your perception clearer, your judgement sounder, and your life closer to your heart's desire".